A case of abnormal architecture - Nicholson, Brian; Logan, Mark (DALHOUSIE MEDICAL JOURNAL, 1997)
16 yr old female with hx. of L parietal stroke in 1988 and hypertension.  Recent medullary infarct with good resolution.